A textile-based wearable system for the assessment of cardiorespiratory signals in altered gravity - Merati, G.; Castiglioni, P.; Veicsteinas, A.; Di Rienzo, M. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
In many sport specialties, gravitational or centrifugal forces may importantly interfere with physiological functions. Werealised a new wearable system, based on textile technology, for the assessment of cardiorespiratory signals and accelerations in sport and work activities performed in altered gravity, through uninterrupted long-term recordings (up to 28 hours), with no interference with the subjects` behaviour. The system, named MagIC, consists of a vest made of cotton and lycra embedding two textile ECG electrodes, a textile piezoresistive transducer for measuring the respiratory frequency, and two small 3D MEMS accelerometers for assessing the subject`s movements and a seismocardiogram (i.e., the recording of body vibrations due to the heart beat). Sensors are connected to a small electronic module placed on the vest which digitalizes signals at 150 Hz, stores data on a memory card and/or wireless transmits them to an external PDA. The system has been previously tested on cardiac patients and healthy subjects during daily life activities. In this study we tested the capability of the system to quantify effects of gravitational stress on the cardiovascular dynamics during parabolic flights and parachute jumps. Parabolic flights were studied in two subjects during a 75 min. flight on board of a modified Boeing 727-200 aircraft. The flight consisted of one parabola at 0.36g, four at 0.16g and ten at 0g. The 0g parabolas were preceded and followed by 1.8g accelerations. The system transmitted ECG and accelerometric data to the PDA without signal loss during the whole flight, with adequate quality to derive a complete tachogram, identify ectopic beats, and correlate heart rate changes with changes of acceleration. We also tested the system by monitoring a parachutist before, during and after a jump. The recording included a 20 min flight, the jump from 4800 m, the phase of the parachute opening, after 1 min of free fall, and landing at see level, 2.5 min after the jump. Also in this test the system recorded the ECG continuously, allowing the evaluation of links between heart rate and gravitational changes occurring during the three major phases of the jump: free-fall, parachute opening, and landing. In both the applications, the comfort of the system was high and the vest never interfered with the subject`s activities, even during the acrobatic manoeuvres in the free-fall phase of the parachute jump. In conclusion, our wearable system was found to be adequate to investigate heart rate dynamics under gravitational stress even for long periods. These results support the use of textile technology in systems for monitoring vital signs in sport and work activities in extreme environments.